Studies on carbon fiber polymer confined slender plain and steel fiber reinforced concrete columns. (1st November 2015) - Dundar, Cengiz; Erturkmen, Duygu; Tokgoz, Serkan
Abstract : Highlights: The experimental behavior of CFRP confined plain and steel fiber reinforced concrete columns has been investigated. CFRP sheets have improved ductility, confinement and deformability and the ultimate strength capacity of columns. CFRP wrapping has exhibited considerable improvement in structural behavior of tested columns. Abstract: This paper presents an experimental research to examine the behavior of carbon fiber reinforced polymer (CFRP) confined plain and steel fiber reinforced concrete columns. In this study, plain and steel fiber reinforced concrete columns were wrapped with CFRP material and experimentally tested to determine the effects of sheets on column behavior. It is revealed that the CFRP material is significantly effective on reinforced concrete columns with respect to strength, ductility and confinement. In addition, a numerical procedure is presented for the analysis of slender reinforced concrete columns confined with CFRP sheets subjected to combined axial load and biaxial bending. The CFRP confined slender reinforced concrete columns have been analyzed using geometric features and experimental parameters of concrete compressive strength, steel yield strength and CFRP material properties to predict the column structural behavior. The analysis and experimental results of CFRP confined slender plain and steel fiber reinforced concrete columns have been achieved in good accuracy in this study.